2021
DOI: 10.1007/s40497-021-00285-y
|View full text |Cite
|
Sign up to set email alerts
|

The antecedents of success among small- and medium-sized enterprises: evidence from Ghana

Abstract: Globally, small-and medium-sized enterprises (SMEs) are regarded as highly crucial to economic growth given their strategic role in job creation and the payment of tax to respective governments. In Ghana for instance, SMEs account for about two thirds of GDP and 92% of businesses. This study investigates the antecedents of success among SMEs in Ghana. It specifically analysed the impact of internal factors, entrepreneurial orientation, managerial competence and technological capabilities, and external factors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…To take advantage of digital capabilities and unique resources, MSMEs should develop strategies to integrate social commerce into their operations to improve their performance and potentially increase their market share (Yacob et al, 2021). Moreover, based on the reviewed literature, policymakers must increase access to digital capabilities and performance among MSMEs to enhance their success (Hagin & Caesar, 2021). This research findings also indicated that financial resources significantly affected SME growth.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…To take advantage of digital capabilities and unique resources, MSMEs should develop strategies to integrate social commerce into their operations to improve their performance and potentially increase their market share (Yacob et al, 2021). Moreover, based on the reviewed literature, policymakers must increase access to digital capabilities and performance among MSMEs to enhance their success (Hagin & Caesar, 2021). This research findings also indicated that financial resources significantly affected SME growth.…”
Section: Discussionmentioning
confidence: 75%
“…The authors suggest that by taking advantage of the digital capabilities and resource uniqueness of MSMEs, the performance of these businesses can be improved. Hagin and Caesar (2021) examined the impact of technological capabilities on small and mediumsized enterprises' performance in Ghana. The study found that MSMEs with higher levels of digital capability and performance had better financial performance and greater growth opportunities.…”
Section: Organization Competency and Performance Of Micro Small And M...mentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies proved that educated entrepreneurs are able to spot opportunities in the market more than others who are uneducated (Fenton and Barry, 2011; Lipset, 2018 as cited by Islam et al, 2019). Also, Hagin and Caesar (2021) ensured that the managerial competence and know-how is vital for business success and its absence will probably lead to business failure even if financial resources available Sallah and Caesar (2020 reported that experience when accompanied with knowledge affect business growth positively. In fact, the absence of knowledge and education create personal challenges.…”
Section: Msar 32mentioning
confidence: 98%
“…Women entrepreneurs face lengthy procedures in obtaining loans (Belwal et al, 2014) and have to handle on high-interest rates (Islam et al, 2019). Hagin and Caesar (2021) proved that access to finance is one of the success factors of entrepreneurs' business and that it affects the business performance. Based on what mentioned the researchers hypothesize that H1.…”
Section: Msar 32mentioning
confidence: 99%